Land Degradation and Desertification: Assessment, Mitigation and Remediation - Zdruli, Pandi; Pagliai, Marcello; Kapur, Selim; Faz Cano, Angel; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Land Degradation and Desertification: Assessment, Mitigation, and Remediation reports research results in sustainable land management and land degradation status and mitigation in 36 countries around the world. It includes background papers with continental and international perspectives dealing with land degradation and desertification studies. The book assembles various topics of interest for a large audience. They include carbon sequestration and stocks, modern techniques to trace the trends of land degradation, traditional and modern approaches of resource-base conservation, soil fertility management, reforestation, rangeland rehabilitation, land use planning, GIS techniques in desertification risk cartography, participatory ecosystem management, policy analyses and possible plans for action. Various climatic domains in Africa, Asia, Europe and The Americas are covered. The book will be of interest to a variety of environmental scientists, agronomists, national and international policy makers and a number of organizations dealing with sustainable management of natural resources.
From the Table of Contents: Introduction -- Background papers -- Land degradationand mitigation in Africa -- Algeria -- Ethiopia -- Kenya -- Morocco -- Nigeria -- South Africa -- Suda -- Tunisia -- Uganda -- Land degradation and mitigation in asia -- China -- India -- Indonesia -- Iran -- Kazakhstan -- Kuwait -- LAO PDR -- Lebanon -- Malaysia -- Thailand -- Turkey -- Yemen -- Land degradation and mitigation in Europe -- Albania -- Austria -- Czech Republic -- Greece -- Italy -- Poland -- Romania -- Spain -- United Kingdom -- Land degradation and mitigation in the Americas -- Argentina -- Bolivia -- Brazil -- Canada -- Mexico -- USA -- Subject Index.
Keywords: Environmental sciences; Climatic changes; Nature Conservation; Soil conservation; Sustainable development; Environment; Nature Conservation; Soil Science & Conservation; Sustainable Development; Environment, general; Climate Change